2018
DOI: 10.13189/saj.2018.060302
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Plyometric Warm-up on Lower Limb Muscle Activity and Time to 10m in the Backstroke Swimming Start

Abstract: The backstroke swim start is an explosive, discrete skill. Swimmers often perform plyometric warm-up protocols, such as repeated jumps, prior to their race. The purpose of this study was to determine the impact of repeated drop jumps performed immediately prior to a backstroke start. Nine elite backstroke swimmers performed three starts after a standard swimming warm-up, and three after an additional plyometric warm-up (three drop jumps from a height of 0.4 m) prior to each start. Timing and peak activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In contrast, swimmers who have produce less power may find the extended setup position where they can take advantage of decreased drag during the flight phase is more appropriate. Building upon our previous research [3,17], the negative correlation between head entry distance and time to 10 m indicates that head entry distance continues to be a valuable, inexpensive tool for coaches to quickly estimate start performance when comparing different start techniques. * Participants 2, 7 and 9 were male.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In contrast, swimmers who have produce less power may find the extended setup position where they can take advantage of decreased drag during the flight phase is more appropriate. Building upon our previous research [3,17], the negative correlation between head entry distance and time to 10 m indicates that head entry distance continues to be a valuable, inexpensive tool for coaches to quickly estimate start performance when comparing different start techniques. * Participants 2, 7 and 9 were male.…”
Section: Discussionmentioning
confidence: 71%
“…Correlations can help identify variables that are closely related to time to 10 m and may be more easily captured by coaches. Our past studies that examined backstroke start equipment changes [3] and warm-up modifications [17] found strong correlations between head entry distance and time to 10 m. Studies completed by other researchers have also shown lower start times which are associated with increased entry distances [5,23]. Although the correlation was only fair in this study, it still supports the relationship between head entry distance and time to 10 m. Accordingly, it is clear that the relationship between head entry distance and start time holds across a wide range of situations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations